Dampak Penebangan Kayu Komersial terhadap Sosial Ekonomi Masyarakat di Kepulauan Mentawai - Juniator Tulius; Myrna Eindhoven (Jurnal Ilmu Kehutanan, 2024)
This research aimed to analyze the effects of commercial logging on the indigenous communities of the Mentawai Islands. Over the past five decades, inhabitants, particularly those residing on Siberut Island, were entangled in a conflict of interest concerning small and large-scale commercial logging activities. The results showed that despite the implementation of regional autonomy in the early 2000s, delegating decision-making authority over natural resource use, local communities and government actively promoted sustainable practices. In the context of the Mentawai Islands, the anticipated outcomes still needed to materialize.